Roseomonas selenitidurans sp. nov., isolated from urban soil, and emended description of Roseomonas frigidaquae. Issue 11 (9th November 2020) - Hou, Xiaoxiao; Liu, Hongliang; Wei, Shuzhen; Ding, Zhongfeng; Sang, Feng; Zhao, Yanfang; Dong, Yuling; Li, Hui; Wang, Qian; Zhao, Juanjuan; Deng, Hongkuan; Zhang, Chunyang; et al.
Abstract : An aerobic, non-motile, Gram-stain-negative, pink, convex, coccobacilli-shaped, mesophilic bacterium, designated strain BU-1 T, was isolated from an urban soil sample from Zibo city, Shandong province, PR China. The strain grew at 20–37 °C (optimum, 30 °C), pH 5–10 (optimum, pH 7) and growth occurred with 0–2 % (w/v) NaCl (optimally with 0.5 %). The results of phylogenetic analysis based on 16S rRNA gene sequences indicated that BU-1 T was closely related to members of the genus Roseomonas and had highest 16S rRNA gene sequence similarities with Roseomonas frigidaquae JCM 15073 T (97.8 %), Roseomonas tokyonensis JCM 14634 T (96.9 %), Roseomonas stagni JCM 15034 T (96.5 %), and Roseomonas riguiloci JCM 17520 T (95.9 %). BU-1 T also formed a subcluster with R. frigidaquae JCM 15073 T and R. stagni JCM 15034 T in phylogenetic trees based on genomic sequences. The genome size of BU-1 T was 5.79 Mb and the DNA G+C content was 71.7 %. ANI, dDDH and AAI values between BU-1 T and R. frigidaquae JCM 15073 T were 84.0, 27.2 and 86.7 %, respectively. Furthermore, the genome of BU-1 T contained 5446 predicted protein coding genes and 4945 (90.8%) of them had classifiable functions. BU-1 T contained Q-10 as the main ubiquinone. The predominant fatty acids (>10 %) were summed feature 3, summed feature 8 and C16:0 . The polar lipid profile contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine and five unidentified aminolipids. Combined data from phenotypic, phylogenetic and chemotaxonomic studies indicated that strain BU-1 T is a representative of a novel species of the genus Roseomonas . Since strain BU-1 T can reduce highly toxic selenite [Se(IV)] to low toxicity elemental selenium [Se(0)], the name Roseomonas selenitidurans sp. nov. is proposed. The type strain is BU-1 T (=KACC 21750 T =GDMCC 1.1776 T ).